A Digitally Programmable Analog Quadrature Sine Oscillator for on-chip Lock-In Measurement Systems - Márquez, Alejandro; Medrano, Nicolás; Calvo, Belén; Martínez, Pedro A. (Jornada de Jóvenes Investigadores del I3A, 2017)
This paper presents a CMOS 1.8V-180nm analog quadrature sine oscillator. Thanks to a custom 12-bit bidirectional DAC-based architecture, the frequency can be digitally programmed over two decades with high accuracy, making it suitable as the actuation system in low-cost high-performance embedded lock-in measurement systems.